Characterization of Sintered Niobium–Alumina Refractory Composite Granules Synthesized by Castable Technology. Issue 8 (3rd June 2022) - Zienert, Tilo; Endler, Dirk; Brachhold, Nora; Weiner, Max; Schmidtchen, Matthias; Prahl, Ulrich; Aneziris, Christos G.
Abstract : Aggregates of niobium–alumina refractory composites are characterized, which are produced by a castable technology followed by a crushing process. Phase separation between niobium and corundum is found for the obtained aggregate classes and the impurity phases NbO and β–Nb2 C are present according to X‐ray diffraction measurements. Among the studied aggregate classes, niobium shows differences in chemistry expressed by the corresponding lattice parameters. The determined morphology and roughness parameters show that the synthesized aggregates are not substantial different independent of their density and porosity. Abstract : Niobium‐alumina composite aggregates are synthesised using casting technology followed by a crushing process. The aggregates of three batches are investigated by means of chemistry (SEM micrographs, XRD phase analysis), sieve analysis, particle size distributions, porosity, morphology and roughness. These data are important for the properties of coarse‐grained castables as well as for improving existing packing models for castable design.